A first and second order cybernetic analysis of barriers facing sexuality education in secondary schools - Swanepoel, Eben Haeser (University of the Free State, 2018)
In light of the growing concern regarding HIV and AIDS, teenage pregnancies, gender violence and suicides among adolescents of alternative sexualities, South African education has become increasingly critical in establishing spaces of inclusivity and promoting acceptance and social justice for inclusivity. Sexuality education was implemented as a subcomponent of the subject Life Orientation, mandatory to all secondary-school learners, as a core initiative to address issues of sexuality and culture that remain rife within South African society. However, the ideal change at societal level has not been realised, with gender inequality and sexuality barriers to social justice remaining prevalent. Research within the area of sexuality education has gained considerable momentum at both national and global levels, exploring the challenges associated with crossing multicultural fissures in bridging the gap between the theoretical ideals of socially just sexuality education and the practical implications thereof within society. This study aims to investigate, from a multicultural contextual approach, how schools implement sexuality education, and the subsequent challenges faced during the teaching thereof. While a wide scope of research explores individual challenges within the system (such as teacher bias, parental objections and textbook restrictions), a systemic perspective is needed to explore the wider suprasystem of South African contexts in order to better comprehend how micro-level challenges arise specific to the place, space and cultures of schools. Responding thereto, this thesis approaches sexuality education from a systemic perspective based on First and Second Order Cybernetics. The initial part of the study encompasses a grounded theoretical approach to gain perspective on the dominant components that inform systemic structure within which sexuality education manifests (specifically drawing on school-level, Exploring Sexuality Education in Secondary Schools community-level and national-level systemic influences). A prominent feedback process that was found to stagnate socially just education, in the form of ‘silence’, emerged, which is further explored within the manner that sexuality education stagnates to adapting national benchmark standards of social justice and inclusivity. After establishing the basis of the desktop reviews, the study empirically analyses, through semi-structured interviews, the views and perspectives of Life Orientation teachers and school management as a means to contextualise the challenges schools face as individual systems and the manner in which they respond to these challenges at wider systemic level. Results point to the way place, space and culture are core mediators of how sexuality education manifests within schools. In conclusion to this thesis, I reflect on my own experiences to the barriers and boundaries to sexuality education that I have experienced during my own teaching career. Through this process of self-reflection, I convey how my pedagogical approach to sexuality education and multicultural teachings have been shaped and adapted within the various systems and subsequent contexts I worked within. Finally, I draw on recommendations which include the need for teachers to engage collaboratively across subject and disciplinary boundaries as a means to promote sexuality education, while also promoting the ongoing need for reflexivity to form the basis of shaping one’s teacher identity, and adaptability of one’s pedagogical methods to best align with the needs of the school system.
Thesis (Ph.D. (School of Education Studies))--University of the Free State, 2018
Keywords: Cybernetics; Sexuality education; Systems analysis; Silence; Cultural diversity; Reflective practice; Multiculturalism